2022
DOI: 10.1049/cvi2.12143
|View full text |Cite
|
Sign up to set email alerts
|

Learning body part‐based pose lexicons for semantic action recognition

Abstract: Semantic action recognition aims to classify actions based on the associated semantics, which can be applied in video captioning and human‐machine interaction. In this paper the problem is addressed by jointly learning multiple pose lexicons based on multiple body parts. Specifically, multiple visual pose models are learnt, and one visual pose model is associated with one body part, which characterises the likelihood of an observed video frame being generated from hidden visual poses. Moreover, multiple pose l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…This indicated that the model had practical value in pose correction. Compared to the action recognition model proposed by Zhou et al [7] and the model proposed by Y Liu et al [8], in the NTU60 RGB+D and NTU120 RGB+D datasets, the average CV index improved by 1.02% and the average CS index improved by 3.5%. In summary, the action recognition model based on MPP-YOLOv3 Tiny network proposed in the study has significant application value in posture correction.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…This indicated that the model had practical value in pose correction. Compared to the action recognition model proposed by Zhou et al [7] and the model proposed by Y Liu et al [8], in the NTU60 RGB+D and NTU120 RGB+D datasets, the average CV index improved by 1.02% and the average CS index improved by 3.5%. In summary, the action recognition model based on MPP-YOLOv3 Tiny network proposed in the study has significant application value in posture correction.…”
Section: Discussionmentioning
confidence: 72%
“…The researchers identified hidden poses in video frames and mapped them to actions in semantic instructions. The experiment outcomes indicated that their solution was effective on multiple datasets [7]. Liu et al learned and put forward a Transformer network for skeleton based human posture recognition.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation